Design And Development of The Cakrawala Project Web Application: Case Study of The Information Technology Division: Perancangan dan Pengembangan Aplikasi Web Proyek Cakrawala: Studi Kasus Divisi Teknologi Informasi - Tirta Subagja; Mamay Syani (FKOM UNIKU, 2025)
This research examines the design and development process of the Cakrawala Project web application using the CodeIgniter framework at the Information Technology Division. The research objectives are to analyze the stages of application development, identify the advantages of using the CodeIgniter framework, and measure the effectiveness of the web application implementation. The research method used is a case study with a Research and Development (R&D) approach through a waterfall development model. The results showed that the use of the CodeIgniter framework in the development of the Cakrawala Project web application provided convenience in the design process through the MVC (Model-View-Controller) architecture, increased development efficiency, and produced responsive web applications. The implementation of the Cakrawala Project web application has succeeded in increasing the effectiveness of information management and collaboration between divisions in the organization. This research contributes practical recommendations in the development of CodeIgniter-based web applications for similar organizational needs.